RETRACTED: Long Noncoding RNA FOXD2-AS1 Promotes the Malignancy of Cervical Cancer by Sponging MicroRNA-760 and Upregulating Hepatoma-Derived Growth Factor - Dou, Xiaoqing; Zhou, Qun; Wen, Mingxiao; Xu, Jiangyan; Zhu, Yingping; Zhang, Shuzhen; Xu, Xianli (Frontiers in Pharmacology, 2020)
Although the functions of long noncoding RNA (lncRNA) called FOXD2 adjacent opposite strand RNA 1 (FOXD2-AS1) have been well studied in multiple human cancer types, its expression status and detailed roles in cervical cancer remain unknown and merit investigation. This study was aimed at assessing FOXD2-AS1 expression in cervical cancer and at determining its effects on the aggressive behavior of cervical cancer in vitro and in vivo. Expression of FOXD2-AS1 in cervical cancer tissues and cell lines was determined via reverse-transcription quantitative PCR. The effects of FOXD2-AS1 on cervical cancer cells were examined by a 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) assay, flow-cytometric analysis, migration and invasion assays, and an in vivo tumorigenicity assay. FOXD2-AS1 was found to be significantly upregulated in cervical cancer tissues and cell lines. High FOXD2-AS1 expression was notably linked with the Federation of Gynecology and Obstetrics (FIGO) stage, lymph node metastasis, and depth of cervical invasion in patients with cervical cancer. Kaplan–Meier survival analysis revealed significantly shorter overall survival of patients when the tumor expression of FOXD2-AS1 was higher in comparison with those in patients with lower FOXD2-AS1 expression. In vitro functional assays revealed that downregulation of FOXD2-AS1 led to suppression of proliferation, migration, and invasiveness as well as to the induction of apoptosis of cervical cancer cells. In addition, FOXD2-AS1 silencing hindered tumor growth in vivo. Mechanism investigation revealed that FOXD2-AS1 functioned as a molecular sponge of microRNA-760 (miR-760). Furthermore, hepatoma-derived growth factor (HDGF) was validated as a direct target gene of miR-760 in cervical cancer cells. Moreover, an miR-760 knockdown reversed the effects of FOXD2-AS1 silencing on cervical cancer cells. FOXD2-AS1 possesses significant oncogenic activity in cervical cancer progression; this activity is mediated by sponging of miR-760 with consequent upregulation of HDGF. The FOXD2-AS1–miR-760–HDGF axis might harbor promising targets for novel treatment strategies of cervical cancer.